FUQAHA SHAFI'IYYAH AND HANABILAH UNDERSTANDING OF THE HADITH OF PROSTRATION MEMBERS IN PRAYER - M. Jakfar, Tarmizi; Najihah Aula, Nur (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2023)
The jurists differ as to the legal status of sticking one's nose to the place of prostration or the floor. These differences of opinion influenced public opinion and opinions, especially during the Covid-19 pandemic. For example, related to the opinion regarding the law of wearing a mask at times because it can cover the nose so that it can cancel the prayer, but there is also an opinion that says that it is permissible to use it. The controversy between whether or not it is permissible to use something that prevents the nose from sticking together when prostrating is conveyed by the Syafi'ī and Ḥanbalī schools. Therefore, this article explains the difference between the Al-Syāfi‘ī school and the Ḥanbalī school in determining the law of sticking the nose when prostrating? and what are the arguments and methods of ijtihad used by the scholars of the Al-Syāfi‘ī and Ḥanbalī schools? This research approach is a qualitative approach, this type of research is normative legal research, while the nature of the data analysis used is the comparative analysis method. The results of this study indicate that the differences between the Al-Syāfi‘ī and Ḥanbalī schools in establishing the law of sticking one's nose during prostration are identified in two points. First, about the legal status. According to the scholars of the Shafi'i school, the nose is not a part of the face that must be attached during prostration, the law is only limited to sunnah. The Hanbali school considers that the nose, the part of the face that must be attached to the ground, is obligatory. Second, about the legal consequences. For the scholars of the Shafi'i school, the legal consequences of praying without sticking your nose are still valid, while according to the Hanbali school it is not valid. The argument of the scholars of the Syafi'i school is the hadith narrated by Imam Al-Bukhari from Ibn Abbas, that the members of prostration are only the forehead, both hands, both knees and both feet. No mention of nose. Then Daruquthni's narration from Jabir, when he saw Rasulullah Saw prostrating with the top of the forehead near the hair. The istinbat method used is the bayani and ta'lili methods. Meanwhile, according to the Hanbali school, the argument used is the history of Imam Al-Bukhari from Ibn Abbas who mentions the Prophet's gesture to point his nose in prostration. Then the narrations of Muslim and Al-Nasa'i regarding the mention of jabhah wa al-anfu (forehead and nose) as members of prostration, in addition to the history of Atsram which states that it is obligatory to stick your nose during prayer. The istinbat method used is the bayani method and the ta'lili method.